Physicochemical Quality and Health Risks Associated with Use of Water from Nyamwamba River, Kasese, Western Uganda - Masereka, Jockus; Byamugisha, Denis; Adaku, Christopher (Asian Journal of Applied Chemistry Research, 2022)
In Kasese district of Western Uganda, farmers cultivating near Nyamwamba River (NR) experience crop wilting whenever the river banks burst. Increased cases of cancer and ulcers in the district is anecdotally blamed on ingestion of contaminated water from water resources polluted by tailings from Kilembe copper mines. Sand miners attested that mining in NR caused body irritations and itching while drinking water from the same river results in abdominal complications in infants. The aim of this study was to assess the seasonal variations in the physicochemical parameters and heavy metals (HMs) content of water from NR, and the associated health risks.
Keywords: Cancer risk; Estimated daily intake; Trace metals.